THE EFFECT OF PROFITABILITY, LIQUIDITY, LEVERAGE, CAPITAL INTENSITY AND FIRM SIZE ON TAX AGGRESSIVENESS WITH MARKET PERFORMANCE AS AN INTERVENING VARIABLE (BANKING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE IN 2014 - 2018) - Adilah Layung Santini; Emmy Indrayani (Universitas Gunadarma, 2020)
This study aims to determine the effect of profitability, liquidity, leverage, capital intensity and firm size on tax aggressiveness with market performance as an intervening variable. The sample used in this study was 43 banks registered on the Indonesia Stock Exchange in 2014 - 2018. This study uses secondary data taken from the banking financial statements, which are processed using amous software. Profitability is proxied with ROA, liquidity with current ratio, leverage with DER, capital intensity with CAP, Size with (Ln total assets), market performance with tobin's q and tax aggressiveness proxied with ETR. The results of this study indicate that profitability, leverage, firm size affect market performance while liquidity and capital intensity do not affect market performance. Profitability, liquidity, leverage, capital intensity and firm size affect tax aggressiveness, tax aggressiveness affect market performance, moderating market performance is not able to strengthen the effect of liquidity and capital intensity on tax aggressiveness and moderating market performance can strengthen the effect of profitability, leverage, firm size towards tax aggressiveness.